2011
DOI: 10.1007/s11606-011-1819-1
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Consequences of Waiting for Health Care in the Veteran Population?

Abstract: National health reform is expected to increase how long individuals have to wait between requests for appointments and when their appointment is scheduled. The increase in demand for care due to more widespread insurance will result in longer waits if there is not also a concomitant increase in supply of healthcare services. Long waits for healthcare are hypothesized to compromise health because less frequent outpatient visits result in delays in diagnosis and treatment. Research testing this hypothesis is sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…A number of previous studies on conditions ranging from peripheral vascular disease to colon cancer have demonstrated that uninsured or under-insured patients present later and with more advanced disease than patients with private insurance resulting in disparities in disease outcomes [58][59][60][61][62][63][64][65]. Timely access to care is particularly important to optimize outcomes for acute conditions in need of rapid definitive treatment such at stroke and myocardial infarction [58,59].…”
mentioning
confidence: 99%
“…A number of previous studies on conditions ranging from peripheral vascular disease to colon cancer have demonstrated that uninsured or under-insured patients present later and with more advanced disease than patients with private insurance resulting in disparities in disease outcomes [58][59][60][61][62][63][64][65]. Timely access to care is particularly important to optimize outcomes for acute conditions in need of rapid definitive treatment such at stroke and myocardial infarction [58,59].…”
mentioning
confidence: 99%
“…Delays in accessing care have occurred for patients seeking outpatient primary and specialty care within VA (U.S. Government Accountability Office, 2012Office, , 2013aOffice, , 2014b. Veterans who received care at VA facilities with longer wait times were at increased risk of adverse long-term health outcomes (e.g., preventable hospitalizations) and intermediate outcomes (e.g., worse hemoglobin A1C levels) than Veterans receiving care at facilities with shorter wait times (Pizer & Prentice, 2011). The increase in wait times and associated adverse health outcomes were responsible, in part, for the greater use of technological methods to deliver care (e.g., messaging between patients and providers, telehealth) (U.S. Government Accountability Office, 2013a), and the development of legislation that expanded VA coverage to allow enrolled Veterans to seek VA-purchased care from community providers.…”
Section: Accessmentioning
confidence: 99%
“…Veterans are less likely than patients in the private sector to report getting appointments as soon as needed. (RAND Health, 2015) In recent years, VA wait times have increased, resulting in a slight decrease in utilization, as well as adverse health outcomes among vulnerable Veterans (Pizer & Prentice, 2011). Delays in accessing care have occurred for patients seeking outpatient primary and specialty care within VA (U.S. Government Accountability Office, 2012Office, , 2013aOffice, , 2014b.…”
Section: Accessmentioning
confidence: 99%
“…These clinical outcomes are not likely to be related to metrics that fail to measure access and unmet health care needs. 8,[13][14][15][16][17][18] Two key lessons emerged from this validation work. First, different access metrics predicted satisfaction for different patient populations.…”
Section: Validation Of Metricsmentioning
confidence: 99%
“…A common strategy to address this problem is to compute facility-level average metrics that exclude the individual patient whose outcome is being assessed. 8,[13][14][15][16][17][18] This is a similar approach to using an instrumental variable analysis that allows consistent estimation of relationships between explanatory variables and outcomes even when key explanatory variables are correlated with the error terms in the models.…”
Section: Validation Of Metricsmentioning
confidence: 99%